Therapeutic use of Guggulsterone in COVID-19 induced obesity (COVIBESITY) and significant role in immunomodulatory effect. (June 2021) - Preethi, L.; Ganamurali, Nila; Dhanasekaran, Dhivya; Sabarathinam, Sarvesh
Abstract: COVID-19 has emerged as a major cause of health crisis around the world. Psychosocial, Behavioral and metabolic changes especially weight gain, among variety of population was produced in this pandemic, through variety of mechanisms. Hyperlipidemia is one of the major issues that result in serious cardiovascular complications. Governmental strategies to minimize the spread of COVID-19 through closures, lockdowns, and alterations in social interaction have complicated weight management efforts. And immunity being the need of the hour has to be improved to prevent the infection. Guggulsterone (GS) isomers are major bioactive compounds present in Commiphora mukul and Commiphora wighti. Guggulsterone shows anti-hyperlipidemic, anti-oxidant, anti-inflammatory, immunomodulatory and appetite regulating activity due to its peculiar characteristics. On the basis of clinical evidence, Guggulsterone seems to possess good cholesterol lowering, appetite regulating as well as immunomodulatory activity which can be beneficial during the pandemic of COVID-19. Highlights: Guggulsterone isomers found to possess cholesterol lowering activity, immunomodulatory effect, and regulates appetite. Guggulsterone antagonizes the Farnesoid X receptor and bile acid receptor to lower the lipid levels. Cytokine storm observed in COVID 19 patients leads to Hyperinflammmation. Guggulsterone inhibits the nuclear factor-κB and reduces severity of Cytokine storm.